Imagining Ireland's self-governed economic future, 1893-1923 - Devlin, Anna Jacqueline (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2025)
The aim of this research was to establish how a self-governed Ireland's economic future had been imagined and evolved during the period 1893-1923 and commence the exploration of the consequent impact on the new state. Along with political and cultural advances, economic plans can have a significant influence on the perception and desirability of independence and play a role in conceptualising an `imagined community'. This research will challenge the common assertion in the literature that there was a failure to engage with economic considerations in the revolutionary period. Two approaches were used to explore Irish society's engagement with economic ideas for self-government. The first examines economic thought at three different levels of society: high, being that of opinion leaders, academics, journalists and politicians in formulating ideas; medium, being that of associational groups discussing and spreading ideas and low, considering the propaganda exposure of the individual to economic data and historical narratives. The second approach examines developments across four dynamic phases: 1893-1911, the period after the defeat of the second Home Rule bill when the possibility of self-government appeared remote; 1912-18, the turmoil of the third Home Rule crisis and Ulster unionist resistance to World War One, the 1916 Rising and the 1917-18 Irish Convention; 1919-21, the setting up, by Sinn Féin, of a system of counter government; 1922-3, the period of Provisional Government and the first year of the Irish Free State. Broad themes, such as land, agriculture, industry, economic development, labour and relationships with Ulster, Britain and its Empire frame the analysis. Providing a new economic perspective on the decades prior to independence, this research reveals the range of influences on and diversity of Irish economic thinking as well as the changing levels of consensus in relation to a self-governed Irish economy. It further tracks continuing effects of pre-Independence economic ideas on Irish Free State economic policies.
APPROVED
Keywords: Economic ideas; Economic policy; Irish Home Rule; Irish Independence